Predicting Life Satisfaction Of Malaysian Chinese Adolescents; The Role Of Similarity In Academic Performance, Academic Self-efficacy And Friendship Satisfaction - Teoh, Ker Hsin (2023)
This study examined the similarities in academic performance, academic self-efficacy and friendship satisfaction of same-sex friends at school predict life satisfaction among Malaysian Chinese adolescents. A total of 238 adolescents (mean age = 15.22) from a SMJK (Cina) located in Penang have participated in this study. This was a quantitative study; participants were required to answer a series of questionnaires. They were asked to identify one same-sex best friend at school and then rate their similarities in academic performance, similarities in academic self-efficacy and friendship satisfaction with that friend. The results revealed that adolescents in this study tend to have best friends who are similar to them. Correlation analysis revealed that friendship satisfaction and similarity in academic self-efficacy was significantly associated with adolescent’s life satisfaction. In addition, correlation analysis also showed that there was a significant association between the similarity in academic self-efficacy and friendship satisfaction. Friendship satisfaction does not serve as the mediator between the similarity in academic performance, academic self-efficacy and life satisfaction. Only similarity in academic self-efficacy was associated with higher life and friendship satisfaction. Findings indicated the importance of friendships in contributing to life satisfaction among Chinese adolescents in Malaysia